PERLINDUNGAN HUKUM TERHADAP TERSANGKA YANG MENGALAMI KEKERASAN OLEH PENYIDIK DALAM PROSES PENYIDIKAN DI KEPOLISIAN RESOR KOTA PEKANBARU - Nurhasanah Nurhasanah; Erdianto Erdianto; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Violence by the investigator is an irony, because the function of criminal procedure law, which seeks to limit the power of the state (police power) in acting and implementing material criminal law, is not implemented properly. The provisions of the criminal procedure law are intended to protect suspects from arbitrary actions by law enforcement officials and the courts.This type of legal research is empirical legal research. Empirical legal research is legal research that examines law that is conceptualized as actual behavior. Meanwhile, if seen from the nature of this research is descriptive. This study uses primary data and secondary data.The result of this research is that the legal protection that can be given to suspects who have become victims as a result of violence perpetrated by the police in the investigation process has been regulated and guaranteed in the 1945 Constitution, the Criminal Procedure Code, the Law on Judicial Power, Law Number 39 1999 on Human Rights. Actions taken or given by the National Police in dealing with police officers who are involved in the use of violence in the investigation process are the persons concerned will be submitted to PROPOS / PROPAM and will be subject to sanctions in the form of demotion or dismissal.Keywords: Legal Protection, Suspects, Violence, Investigators